Role of bank credit on local growth: Do politics and crisis matter? - Önder, Zeynep; Özyıldırım, Süheyla (Journal of Financial Stability, 2013)
Although state-owned banks are expected to promote the growth of less-developed regions, especially in developing economies, several cross-country studies report that lending by state banks is associated with the inefficient allocation of credit and low levels of development. Further, state banks have been found to lend to their cronies, especially around elections. In this paper, we study the lending activities of state-owned and private banks during the period 1992–2010 and analyze the relationship between the credit these banks provide and local economic growth in Turkey during crisis periods and in election years. We find that the share of state-owned banks in the credit market in crisis periods and local election years is significantly higher than their share in non-crisis and non-election periods. The per capita real credit that state-owned banks provide during crisis years is found to be positively associated with local growth in all provinces. Our results suggest that although state-owned banks might issue loans for political reasons in election periods, they also seem to play an important role in offsetting the adverse effects of economic shocks, especially in developed provinces.